Content Analysis of Sharia Da’wah Messages on The Instagram Account @Lensamu During The Period Of Ramadan 1446 H - Muhammad, Dzulfikri; Dewi, Maya Sandra Rosita (JAWAB: Journal of Asian World and Islamic Behavior Journal of Asian World and Islamic Behavior, 2026)
Instagram has become a social media platform used for preaching. One example is the @lensamu account belonging to the Muhammadiyah organization. This study aims to analyze the sharia preaching messages on the Muhammadiyah Instagram account @lensamu. The study uses a qualitative paradigm with a descriptive content analysis method based on Klaus Krippendorff's Content Analysis concept. The research period was during the month of Ramadan 1446 AH (February 28–March 30, 2025). The results showed that there were 26 pieces of content that fell into the category of Sharia preaching messages, which were divided into two main categories, namely worship and society. In the worship category, the preaching messages covered the themes of faith, prayer, zakat, and fasting, which aimed to encourage an increase in the quality of worship during Ramadan. Meanwhile, in the social category, the da'wah messages focused on muamalah aspects that emphasized social roles and encouraged doing good to others. Overall, the da'wah content of @lensamu was oriented towards strengthening personal worship and forming social ethics in line with the values of amar ma'ruf nahi munkar.